2 - 3 gadus vecu bērnu acu-roku koordinācijas sekmēšana tēlotājdarbībā pirmsskolā - Iricjana, Zarema (Latvijas Universitāte, 2017)
2-3 gadus vecu bērnu acu-roku koordinācijas sekmēšana tēlotājdarbībā pirmsskolā. Darba mērķis ir teorētiski noskaidrot un praktiski pārbaudīt kā speciāli izstrādātu uzdevumu kopa tēlotājdarbībā veicina 2-3 gadus vecu bērnu acu-roku koordinācijas attīstību. 2-3 g.v. bērnu acu-roku koordinācija tēlotājdarbībā pirmsskolā sekmēsies, ja skolotājs pievērsis uzmanību : •mācīšanās procesu organizacijai – tā kā katram bērnam ir savs mācīšanās ātrums, sava pieredze, tad ir jāpielieto individuāla pieeja katram bērnam; •bērnu vecumposmu attīstības īpatnībam; •izstrādātiem uzdevumiem – visiem jābut atbilstošiem bērnu vecumam un spējam; •visas dienas garumā izmantot pirkstu rotaļas, spēles un ļaut bērniem biežāk izmantot dažādus acu-roku koordinacijas palīglīdzekļus. Darbā ir 53 lappuses, 19 tabulas, 9 attēli, 11 pielikumi, izmantoti 32 literatūras avoti.

2-3 years old children’s hand-eye coordination promotion in the creative activities in preschool. Jobs target is theoretically find out and practically check how specally designed set of tasks in the creatitive activities promotes 2-3 years old chield hand-eye coordination development. In the first and second part of the work the scientific and pedagogical literature is analysed about hand-eye coordination promotion in the creative activities in preschool. The third part describes on empirical study and describes the obtaised results. The study found the answer to the guestion asked. How promotion in the creative activities in preschool promotes 2-3 years old childs hand-eye coordination? 2-3 years old childs hand-eye coordination in the creative activities in preschool will be successful, if teacher will pay attention: •the organization of teaching processes – sincl every child has his own learning speed and experience, then you need to apply an individual appreach to each child; •child peculiarities of davelopment of age groups; •designed tasks – all must be apprepriate for the age and abilities of the child; •use finger games, games and allow children to use different hand-eye coordination tools more aften throughout the day. The paper contains 53 pages, 19 tables, 9 figures, 11 appendices, 32 literary sources have been used.
2-3 years old children's hand-eye coordination promotion in the creative activities in preschool
Keywords: Pirmsskolas pedagoģija; acu-roku koordinācija; tēlotājdarbība; pirmsskola; sekmēšana